TYPE 2 DIABETES MELLITUS PREDICTION IN MALAYSIA USING MODIFIED DIABETES RISK ASSESSMENT TOOL - Aung Myo Oo; Al-abed Ali Ahmed Al-abed; Ohn Mar Lwin; Sowmya Sham Kanneppady; Tee Yee Sim; Nor Ashikeen Mukti; Anis Safirah Zahariluddin; Faizul Jaffar (Malaysian Journal of Public Health Medicine, 2020)
Type 2 diabetes mellitus (DM) is becoming major health threat worldwide and it is extremely common in clinical setting. Malaysia is one of the highest diabetic populations among Asian countries and the new cases are increasing day to day. Early detection of people with high risk of Type 2 DM by using simple, easy and cost-effective assessment tool is the better way to identify and prevent the community from this non-communicable disease. The objectives of the study were to identify those are high risk to become type 2DM among Malaysians by using risk scoring form and to educate them how to prevent it. Total 591 subjects were recruited from the health screening programs carried out by the collaboration of Petaling Jaya Development Council (MBPJ) and Lincoln University College, Malaysia. Modified form of Finnish Type 2 Diabetes Risk Assessment Tool was used to identify people at risk of becoming type 2 DM. Descriptive analysis was performed for all included variables in this study by using SPSS version 21. The study found out that almost half of the participants were found to have family history of DM, 60% of them were overweight and obese and 47% were having above normal waist circumference. We observed that nearly 60 % of participants in the study were having moderate to high risk of becoming type 2 DM in next 10 years. To conclude, the result of our study would be helpful in implementation of cost-effective, convenient Type 2 DM risk assessment tool which has yet to be implemented in Malaysia.